2003
DOI: 10.1007/s00049-003-0236-2
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of pyrrolizidine alkaloids by the harvestman Mitopus morio (Phalangidae) a predator of alkaloid defended leaf beetles

Abstract: Summary. The harvestman Mitopus morio (Phalangidae) is a generalist predator. It is known to prey on larvae of the chrysomelid leaf beetle Oreina cacaliae defended by plant acquired pyrrolizidine alkaloids (PAs). Tracer feeding experiments were performed to determine how harvestmen tolerate protoxic PAs. Minced meat containing either [ 14 C]senecionine or [ 14 C]senecionine N-oxide was fed to M. morio and subsequently feces and bodies were analyzed. Labeled alkaloid N-oxide remained stable and was eliminated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Tropane alkaloids are effective against monkeys but not spiders . Hartmann et al (2003) verified that the harvestman Mitopus morio (Phalangidae), a generalist predator, which eats the larvae of the pyrrolizidine alkaloidcontaining Oreina cacaliae (Coleoptera: Chrysomelidae), is able to detoxify these compounds. Why are some compounds active against some predators and inactive against others, as reported here for Methona themisto caterpillars?…”
Section: Discussionmentioning
confidence: 95%
“…Tropane alkaloids are effective against monkeys but not spiders . Hartmann et al (2003) verified that the harvestman Mitopus morio (Phalangidae), a generalist predator, which eats the larvae of the pyrrolizidine alkaloidcontaining Oreina cacaliae (Coleoptera: Chrysomelidae), is able to detoxify these compounds. Why are some compounds active against some predators and inactive against others, as reported here for Methona themisto caterpillars?…”
Section: Discussionmentioning
confidence: 95%
“…The ants are common visitors of extrafloral nectaries of Crotalaria pallida, a host plant of U. ornatrix (Ferro et al 2006). Hartmann et al (2003) verified that the harvestman Mitopus morio (Opiliones: Phalangidae), feeding on a diet treated with PAs, was able to N-oxidize and excrete the PAs. The harvestman is the main predator of the PA-containing leaf beetle larvae O. cacaliae in their natural environment.…”
Section: Hägele and Rowell-rahier (2000)mentioning
confidence: 78%
“…Some predators and parasitoids can overcome the PAs and are able to feed on PA specialist phytophagous insects. Predators may be able to feed and to detoxify PAs as has been studied by Glendinning et al Phytochem Rev (2011) 10:83-98 93 (1990 for vertebrates, and Hartmann et al (2003) for a harvestman predator. These authors showed that some predators might present similar behavioural or physiological mechanisms that enable them to overcome toxic compounds.…”
Section: Discussionmentioning
confidence: 97%
“…However, there are relatively few well-studied examples of predator physiological adaptation to such prey (e.g. Geffeney et al, 2002;Hartmann et al, 2003). This stands in contrast to the large body of work on the adaptations of herbivores to plant chemical defences (Brattsten, 1992;Li et al, 2007).…”
Section: Introductionmentioning
confidence: 98%